Novel approaches to imaging epilepsy by MRI. (May 2009) - Hetherington, Hoby
As the concept of a network of injury has emerged in the treatment of epilepsy, the importance of evaluating that network noninvasively has also grown. Recently, studies utilizing magnetic resonance spectroscopic imaging, manganeseenhanced MRI and functional (f)MRI measures of resting state connectivity have demonstrated their ability to detect injury and dysfunction in cerebral networks involved in the propagation of seizures. The ability to noninvasively detect neuronal injury and dysfunction throughout cerebral networks should improve surgical planning, provide guidance for placement of devices that target network propagation and provide insights into the mechanisms of recurrence following resective surgery.